Physiological effects of providing supplemental air for avalanche victims. A randomised trial. - Wik, Lars; Brattebø, Guttorm; Østerås, Øyvind; Assmus, Jörg; Irusta, Unai; Aramendi, Elisabete; Mydske, Sigurd; Skaalhegg, Tore; Skaiaa, Sven Christjar; Thomassen, Øyvind (Resuscitation, 2022)
Background: Survival from avalanche burial is dependent on time to extraction, breathing ability, air pocket oxygen content, and avoiding rebreathing of carbon dioxide (CO2). Mortality from asphyxia increases rapidly after burial. Rescue services often arrive too late. Our objective was to evaluate the physiological effects of providing personal air supply in a simulated avalanche scenario as a possible concept to delay asphyxia. We hypothesize that supplemental air toward victim's face into the air pocket will prolong the window of potential survival.Methods: A prospective randomized crossover experimental field study enrolled 20 healthy subjects in Hemsedal, Norway in March 2019. Subjects underwent in randomized order two sessions (receiving 2 litres per minute of air in front of mouth/nose into the air pocket or no air) in a simulated avalanche scenario with extensive monitoring serving as their own control.Results: A significant increase comparing Control vs Intervention were documented for minimum and maximum end-tidal CO2 (EtCO2), respiration rate, tidal volume, minute ventilation, heart rate, invasive arterial blood pressures, but lower peripheral and cerebral oximetry. Controls compared to Intervention group subjects had a lower study completion rate (26% vs 74%), and minutes in the air pocket before interruption (13.1 ± 8.1 vs 22.4 ± 5.6 vs), respectively.Conclusions: Participants subject to simulated avalanche burial can maintain physiologic parameters within normal levels for a significantly longer period if they receive supplemental air in front of their mouth/nose into the air pocket. This may extend the time for potential rescue and lead to increased survival.